Electrical properties of nanoscale p-n heterojunctions formed between a single ZnO nanorod and GaN substrate. (1st March 2020) - Tiagulskyi, Stanislav; Yatskiv, Roman; Faitová, Hana; Kučerová, Šárka; Vaniš, Jan; Grym, Jan
Abstract: We study electronic transport in single vertically oriented n-type ZnO nanorods on p-type GaN substrates using a nanoprobe in a scanning electron microscope. The ZnO nanorods are prepared by chemical bath deposition on both plain GaN substrates and the substrates locally modified by focused ion beam. The heterojunctions on focused ion beam-modified substrates show rectifying current-voltage characteristics, while the characteristics of the plain structures are symmetrical. Adsorption/desorption processes on the surface of ZnO nanorods strongly affect their electrical properties. We demonstrate that the electronic transport in the nanorods grown on focused ion beam-modified substrates is less sensitive to adsorption/desorption processes, which is related to their uniform nucleation and higher crystalline quality.